Multilayered Low Temperature Cofired Ceramics (LTCC) Technology - Imanaka, Yoshihiko; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
In recent years, Low Temperature Cofired Ceramics (LTCC) have become an attractive technology for electronic components and substrates that are compact, light, and offer high-speed and functionality for portable electronic devices such as the cellular phones, personal digital assistants (PDA) and personal computers used for wireless voice and data communication in rapidly expanding mobile network systems. LTCC are especially suitable for the high frequency circuits required for high-speed data communications. LTCCs are made by combining ceramic insulating materials, conductor materials, and other materials through numerous processes culminating in co-firing. The materials and the processes used are therefore interdependent. By ensuring the consistency between materials and processes, it is possible to achieve circuit boards and various types of high frequency passive components and so on with the desired characteristics. This book describes the general technical information of each material (ceramic, conductor, and resistor materials) and each process, and it offers commentaries on unique examples resulting from these interrelations.
The Possibility of High Frequency Functional Ceramics Substrate -- Material technology -- Ceramic material -- Conducting material -- Resistor materials and high K dielectric materials -- Process technology -- Powder preparation and mixing -- Casting -- Printing and laminating -- Cofiring -- Reliability -- Future of LTCCs.
Keywords: Materials science; Electronics; Microelectronics; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Ceramics, Glass, Composites, Natural Methods; Electronics and Microelectronics, Instrumentation; Characterization and Evaluation of Materials; Electronic books